2010
DOI: 10.1016/s1607-551x(10)70090-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide‐stimulated Leukocytes Contribute to Platelet Aggregative Dysfunction, Which is Attenuated by Catalase in Rats

Abstract: Endotoxemia causes several hematological dysfunctions, including platelet degranulation or disseminated intravascular coagulation, which lead to thrombotic and hemorrhagic events. Here, we tested the hypothesis that bacterial lipopolysaccharide (LPS)-stimulated leukocytes contribute to platelet aggregative dysfunction, and this function is attenuated by antioxidants. Platelet-rich plasma (PRP) was prepared from whole blood of normal and endotoxemic rats. The ability of platelet aggregation was measured by an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In the present study, experimental endotoxemia, by means of a 4-hour infusion of 0.5 ng/kg/hour LPS, reduced primary hemostasis (platelet aggregation, reduced by Multiplate) and enhanced secondary hemostasis (clot formation) in whole blood (reduced R time (enhanced coagulation initiation) and increased G (enhanced clot strength) at 4 h by TEG) in accordance with previous findings [23][25], [27][29]. During endotoxemia, fibrinolysis was enhanced (increased breakdown of the platelet-fibrin clot, CLT reduced at 4 h by TEG), which probably explains the observed reduction in the functional fibrinogen level (reduced strength of the fibrin clot, MA reduced at 4 h by FF).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, experimental endotoxemia, by means of a 4-hour infusion of 0.5 ng/kg/hour LPS, reduced primary hemostasis (platelet aggregation, reduced by Multiplate) and enhanced secondary hemostasis (clot formation) in whole blood (reduced R time (enhanced coagulation initiation) and increased G (enhanced clot strength) at 4 h by TEG) in accordance with previous findings [23][25], [27][29]. During endotoxemia, fibrinolysis was enhanced (increased breakdown of the platelet-fibrin clot, CLT reduced at 4 h by TEG), which probably explains the observed reduction in the functional fibrinogen level (reduced strength of the fibrin clot, MA reduced at 4 h by FF).…”
Section: Discussionsupporting
confidence: 93%
“…This has been documented by TEG/ROTEM and has been reproduced in studies using experimental human [23] and animal [25][27] models of endotoxemia [23], [25][27]. Also, platelet aggregation is profoundly reduced in septic patients [19][22] and decreases with disease severity [20]–[22], which has also been reproduced in experimental human [23], [24] and animal [28], [29] models of endotoxemia.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies have shown that O 2 - reduces the threshold for platelet activation to collagen [ 14 ]. In addition, Dong et al showed that catalase in vitro reduces the likelihood of platelet dysfunction during LPS-induced sepsis [ 41 ]. In the present study, using SOD and catalase, we demonstrated that reactive oxygen species, such as O 2 - and H 2 O 2 do indeed contribute to enhancement of platelet function followed acute exposure to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet count was determined by an electronic counter (Sysmex Microcellcounter F-800; Toa Medical Electronics, Kobe, Japan). The platelet count in the PRP was adjusted to 400,000/μL by dilution with PPP as needed [5,6,7,8]. Platelet aggregation in PRP was induced by 2.5 μM ADP and measured with an aggregometer (PACKS-4 platelet aggregation chromogenic kinetic system; Helena Laboratories, Beaumont, TX, USA).…”
Section: Methodsmentioning
confidence: 99%